New Insight into Biofilm Formation Ability, the Presence of Virulence Genes and Probiotic Potential of Enterococcus sp. Dairy Isolates - Popović, Nikola; Dinić, Miroslav; Tolinački, Maja; Mihajlović, Sanja; Terzić-Vidojević, Amarela; Bojić, Svetlana; Djokić, Jelena; Golić, Nataša; Veljović, Katarina (Frontiers in Microbiology, 2018)
Enterococci have controversial status due to their emerging role in nosocomial infections and transmission of antibiotic resistance genes, while some enterococci strains are used as probiotics for humans and animals and starter cultures in dairy industry. In order to improve our understanding of factors involved in the safe use of enterococci as potential probiotics, the antibiotic susceptibility, virulence and probiotic traits of 75 dairy enterococci isolates belonging to Enterococcus durans (50), En. faecium (15), En. faecalis (6), En. italicus (3) and En. hirae (1) were evaluated. The results revealed that ciprofloxacin resistance and biofilm formation are correlated with isolates originated from Golija mountain (Serbia), while gelatinase activity was more common in isolates from Prigorje region (Croatia), pointing to uncontrolled use of antibiotics and anthropogenic impact on dairy products’ microbiota in these regions. The virulence genes were sporadically present in 13 selected dairy enterococci isolates. Interestingly, biofilm formation was correlated with higher ability of strains to reduce the adhesion of E. coli and Salmonella Enteritidis to HT29-MTX cells. To our knowledge this is the first study reporting the presence of the esp gene (previously correlated with pathogenesis) in dairy enterococci isolates, mostly associated with the genes involved in adhesion property. Hence, the results of this study revealed that the virulence genes are sporadically present in dairy isolates and more correlated to adhesion properties and biofilm formation, implicating their role in gut colonization rather than to the virulence traits.